Monterey Street (1930)
Monterey Street in the 1930s, looking north from Chorro Street. To the right (in order of distance) is The Florsheim Shoe, the Sinsheimer Bros. building, a hardware store, the Mission Hotel, the Bee Hive Cafe, the Anderson Hotel, and other coffee shops, hotels, drugstores, and gas stations. To the left (in order of distance) is the Blackstone Hotel, A. Sauer Co. Grocers and Bakers, the Wilson Hotel, Austin's Candy Store, and in the distance "Coffee Tavern", "Hotel Andrews", and other businesses including an auto shop.